2017
DOI: 10.1039/c7nr06959f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ultrasmall CsPbBr3 nanoclusters and their transformation to highly deep-blue-emitting nanoribbons at room temperature

Abstract: Discretely sized semiconductor clusters have attracted considerable attention due to their intriguing optical properties and self-assembly behaviors. While lead halide perovskite nanostructures have been recently intensively explored, few studies have addressed perovskite clusters and their self-assembled superstructures. Here, we report the room-temperature synthesis of sub-2 nm CsPbBr clusters and present strong evidence that these ultrasmall perovskite species, obtained under a wide range of reaction condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 29 publications
3
65
0
Order By: Relevance
“…The 3D precipitated from the 0.5 M DMSO solution is likely due to the high concentration that results in significant interaction between adjacent octahedra after the addition of the antisolvent. 35 In fact, upon direct addition of the antisolvent, we observed a white precipitate, which is most probably in the 0D phase or ultrasmall 3D clusters 36 that in a few seconds turned into orange-colored 3D perovskites.…”
Section: Resultsmentioning
confidence: 80%
“…The 3D precipitated from the 0.5 M DMSO solution is likely due to the high concentration that results in significant interaction between adjacent octahedra after the addition of the antisolvent. 35 In fact, upon direct addition of the antisolvent, we observed a white precipitate, which is most probably in the 0D phase or ultrasmall 3D clusters 36 that in a few seconds turned into orange-colored 3D perovskites.…”
Section: Resultsmentioning
confidence: 80%
“…Various approaches have recently been developed to achieve synthetic control of the composition, size, and shape of perovskite NCs to obtain emissions covering the whole visible spectrum, from deep blue to near-infrared (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). For instance, by manipulating the quantum size effect, the emission of CsPbBr 3 NCs can be tuned from green for NCs with sizes larger than the exciton bohr radius (~7 nm) to deep blue for quantum dots, nanowires, and nanoplatelets with strong quantum confinement (15)(16)(17)(18)(19)(20). Several recent studies have demonstrated NC size control within the quantum confinement regime by introducing organic salts (21), controlling the acid-base environment (22), varying Pb-to-halide ratio (23), etc.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is particularly serious in the preparing deep blue PeLED device. 2) Perovskite quantum dot, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] a nano-sized perovskite encapsulated by a long chain of oleic acid, turns a large-scale crystal into a small quantum dot. For the quantum confinement effect, [45] the long chain conjugation of metal halide is inhibited, which shows a wide bandgap and high quantum efficiency of luminescence.…”
mentioning
confidence: 99%